Musashi expression in intestinal stem cells attenuates radiation-induced decline in intestinal permeability and survival in Drosophila. - Sharma, A.; Akagi, K.; Pattavina, B.; Wilson, K.A.; Nelson, C.; Watson, M.; Maksoud, E.; Harata, A.; Ortega, M.; Brem, R.B.; Kapahi, P. (Scientific reports, 2020)
Exposure to genotoxic stress by environmental agents or treatments, such as radiation therapy, can diminish healthspan and accelerate aging. We have developed a Drosophila melanogaster model to study the molecular effects of radiation-induced damage and repair. Utilizing a quantitative intestinal permeability assay, we performed an unbiased GWAS screen (using 156 strains from the Drosophila Genetic Reference Panel) to search for natural genetic variants that regulate radiation-induced gut permeability in adult D. melanogaster. From this screen, we identified an RNA binding protein, Musashi (msi), as one of the possible genes associated with changes in intestinal permeability upon radiation. The overexpression of msi promoted intestinal stem cell proliferation, which increased survival after irradiation and rescued radiation-induced intestinal permeability. In summary, we have established D. melanogaster as an expedient model system to study the effects of radiation-induced damage to the intestine in adults and have identified msi as a potential therapeutic target.